Analysis of the performance of domestic lighting lamps - Aman, M.M.; Jasmon, G.B.; Mokhlis, Hazlie; Bakar, A.H.A. (Energy Policy, 2012)
The power crisis problem is getting worse in the developing countries. Measures are being taken to overcome the power shortage problem by efficiently utilizing the available power. Replacement of high-power consumption lamps with energy efficient lamps is also among these steps. This paper presents a detailed comparative analysis between domestic lighting lamps (DLLs) use for producing artificial light. DLLs include incandescent lamp (IL), fluorescent lamp (FL) and compact fluorescent lamp (CFL). Light emitting diodes (LED) based lamp technology is relatively new in comparison with conventional incandescent and discharge lamps. However, the present study will also cover the LED lamps. Power quality based experiments have been conducted on DLLs in Power System Laboratory and power consumption based calculations are carried out using the lighting design software DIALux. The result shows that with the current technology, the use of FL and LED lamp is beneficial for utility as well as for consumer. However, with the current pace in the development of LED technology, it is possible LED lamps will lead the lighting market in the near future. The paper has also presented the uncertainties that exist in lighting market and proposed the guidelines that will help in making future energy policy.